Runoff Analysis Based on Rainfall in Gegesik Irrigation Area - Delia Ichsania; Hardia Adiguna; Syaihu Akhmad Syaihu; Nurdiyanto Nurdiyanto; Sulistijo Edhy Purnomo (Jurnal Indonesia Sosial Teknologi, 2025)
The amount of runoff water flow needs to be calculated based on rainfall data in the region. This research aims to analyze rainfall data to obtain the amount of runoff discharge in the Gegesik irrigation area. In this study using a quantitative approach. The research begins with conducting field surveys and collecting data from related agencies. The method used in analyzing rainfall data uses the Thiessen polygon method to obtain regional rainfall and the NFR method to obtain irrigation water requirements. Based on the analysis of rainfall data using the Thiessen polygon method, it can be seen that the average value of rainfall area in 10 years is 42.32 mm. So it can be known that the need for irrigation water with the NFR method occurs in November, which is 12.67 mm/day. After analyzing these results, it can be seen that the existing discharge is 0.77 m3 / s, the flood discharge that occurs is 1.24 m3 / s and the runoff discharge is 0.47 m3 / s. After the embankment elevation of 1 m, it can be seen that the discharge is 0.999 m3 / s, it can be concluded that the discharge capacity after making the embankment can accommodate the runoff discharge. So to reduce water runoff into rice fields from the research that has been done, it can be suggested to change the dimensions of irrigation with the initial height of the embankment of 0.84 m to 1 m and the need for dredging because of the large amount of sediment that settles in irrigation channels that can cause water to run over into the fields.